Separation of Biobutanol from Fermentation Solutions by Perstraction Using p6 6 6 14][Tf2n] as Receiving Phase: Phase Temperature Analysis - Romero-Figueroa, J; Quijada-Maldonado, E (Italian Association of Chemical Engineering - AIDIC, 2022)
In this work, the perstraction process was implemented to separate butanol, acetone and ethanol from a model fermentation aqueous solutions using [P6, 6, 6, 14][Tf2N], which is a highly hydrophobic phosphonium based ionic liquid as receiving phase. Perstraction assays were carried out using a flat sheet dense membrane of polydimethylsiloxane (PDMS) to quantify the extraction percentage, transmembrane fluxes of butanol, water and butanol/water selectivity focused on the effect of the temperature difference between the feed and extractant phase. The results indicate that the fluxes of butanol were particularly high considering the PDMS membrane used in the experiments was relatively thick (160 μm). The highest average flux of butanol was obtained when the temperature of the aqueous phase was 60 °C and the temperature of the organic phase was 30 °C reaching a value of 6.3 ∙ 10-3 kg h−1 m−2, showing a butanol-water selectivity of 58.2, generated by the different sensitivity to temperature of the vapor pressure of both compounds. Finally, this disruption technique combined with ILs could allow the design of a wide range of separation processes for purify a wide variety of molecules. In addition to this, the perstraction process could be considered as a good alternative for the selective separation of fermentation or reaction products with high commercial value. © 2022 Italian Association of Chemical Engineering - AIDIC. All rights reserved.